Evolution Study Of Solar Like Star τ Ceti Using Mesa Program - Mumtahana, Farahhati; Nurzaman, M. Zamzam; Putri, Gerhana Puannandra; Zulfiana, Ahmad (Indonesian Journal of Aerospace, 2024)
Tau (τ) Ceti is a G8V class star that has similarities to the sun and several comparable physical properties, although in general its value is smaller and not as active as the sun. Similarities also occur in the planetary system, which has been studied and confirmed to be terrestrial types, four of them were confirmed in the Habitable Zone. This paper aims to study the evolutionary traces of the star Ceti related to the initial studies of its influence on the planetary system through modelling experiments. Interior structure modelling and evolution were carried out with the MESA program. The study of stars belonging to population II begins with the determination of several fundamental parameters obtained from observations such as interferometry and spectroscopy from several references and calculations, which are then used as input in building the model. Static modeling has been carried out by the current condition of the star in the main sequence phase with an age of 9.5 Gyr producing various physical parameters and the division of the star’s atmospheric zone. The evolutionary modelling was carried out up to the Asymptotic Giant Branch (AGB) stage, related to the initial studies of its relationship to the planetary system. Result shows that, without consideration of planetary tidal effect, three of the four planets are likely to be affected by the evolution of τ Ceti. Even though the simulation was only carried out up to the AGB stage, the end history of τ Ceti will be similar to a Solar-mass star, yet over a longer period of time than the Sun.